The popularity of tabloids: a reception analysis of the Daily Sun amongst Grahamstown readers - Mapudzi, Hatikanganwi (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2009)
Tabloid journalism has and continues to spark controversy. Scholarly considerations of tabloid journalism often question its contribution to democratic causes. However, little academic attention has been given to the question of how tabloids are understood and evaluated by their audiences. This study considered a range of audience responses to the Daily Sun by analysing the way some of its readers understand and evaluate it. The study examined the appeal of this popular tabloid to some Grahamstown readers. Reception analysis was employed to determine why these people read the Daily Sun. In particular, the active audience theory was used as a framework to conduct the research. To achieve the objectives of the study, qualitative research methods such as focus group interviews and individual in-depth interviews were employed. Looking at the findings, many of the respondents acknowledged they read the tabloid for interpersonal communication, diversion and entertainment. The results also revealed that their lived context plays a major role in their reading of stories. In a wider context, the research contributes to an understanding of the popularity of tabloid newspapers.
Keywords: Daily Sun; Tabloid newspapers -- South Africa; Tabloid newspapers -- South Africa -- Circulation; Local mass media -- Research -- South Africa; Readership surveys -- South Africa -- Grahamstown